2021
DOI: 10.1002/lno.11740
|View full text |Cite
|
Sign up to set email alerts
|

Selective feeding and linkages to the microbial food web by the doliolidDolioletta gegenbauri

Abstract: Gelatinous zooplankton play a crucial role in pelagic marine food webs, however, due to methodological challenges and persistent misconceptions of their importance, the trophic role of gelatinous zooplankton remains poorly investigated. This is particularly true for small gelatinous zooplankton including the marine pelagic tunicate, Dolioletta gegenbauri. D. gegenbauri and other doliolid species occur persistently on wide subtropical shelves where they often produce massive blooms in association with shelf upw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 69 publications
3
32
0
Order By: Relevance
“…Degraded DNA can lead to underestimates of prey abundances (Nejstgaard et al 2008), thus should be quantified. For example, Frischer et al (2014) tested the degree to which doliolids degrade diatom DNA using a differential length amplification qPCR (dla-qPCR) assay and found little DNA degradation, which supported additional studies that compared the doliolid diatom concentration factor across many life stages (Walters et al 2019) and numerous other phytoplankton taxa (Frischer et al 2021). Such analysis of DNA degradation levels would be a precursor to studies in other pelagic tunicate taxa and microorganisms.…”
Section: Quantitative Pcrmentioning
confidence: 70%
See 3 more Smart Citations
“…Degraded DNA can lead to underestimates of prey abundances (Nejstgaard et al 2008), thus should be quantified. For example, Frischer et al (2014) tested the degree to which doliolids degrade diatom DNA using a differential length amplification qPCR (dla-qPCR) assay and found little DNA degradation, which supported additional studies that compared the doliolid diatom concentration factor across many life stages (Walters et al 2019) and numerous other phytoplankton taxa (Frischer et al 2021). Such analysis of DNA degradation levels would be a precursor to studies in other pelagic tunicate taxa and microorganisms.…”
Section: Quantitative Pcrmentioning
confidence: 70%
“…Sequencing-based approaches can be applied to grazing questions in two ways. First, direct sequencing of dissected tissue from feeding organs of pelagic tunicates can reveal the taxonomic range of grazed prey and any feeding selectivity (Walters et al 2019;Frischer et al 2021;Thompson et al 2021). Second, coupling of sequencing to in situ incubation experiments can reveal diversity in retained prey, clearance rates, and enable comparative analysis between coexisting tunicate taxa (Dadon-Pilosof et al 2017).…”
Section: Sequencingmentioning
confidence: 99%
See 2 more Smart Citations
“…This shift may favor salps over krill, as krill are less effective than salps at feeding on small cell sizes 31 . Recent studies found indications for selective feeding of doliolids, a group closely related to salps, in the Atlantic Ocean 32 , and suggested that the diet of Mediterranean salps is determined by prey taxonomy, rather than size 33 . Yet, there are no recent studies on the diet of salps in the Southern Ocean and studies that simultaneously compare the diet composition of krill and salps from the same region are lacking.…”
mentioning
confidence: 99%